Gestão ambiental em espaços de lazer e turismo na Lagoa do Apodi/RN - Chaves, Maria Liliane de Queiroz (Universidade Federal Rural do Semi-Árido, 2018)
The Lagoa do Apodi-RN along the Boardwalk, located on its banks, are known to form together an important tourist terminal, known for providing locals and visitors with different forms of leisure and recreation. But the development of such activities without proper planning can represent risks of environmental degradation to pond and your surroundings. In this way through this study sought to identify the main leisure and recreation activities developed in the lagoon and in your surroundings as well as the impacts caused to this environment, be they environmental noise pollution and water quality, or economical as generation of employment and income, due to the same. For this semi-structured questionnaires were applied with the attributes (socioeconomic profile), behavioral (environmental perception) and attitudes (environmental practices), the agents of these services. It was noted that bars and restaurants are considered the main forms of leisure activities in the study area, being developed limited sustainability actions by enterprises investigated. It was evidenced that the users of the Lake for recreational purposes have shown concern with your state of degradation, pointing the dump untreated domestic wastewater and solid waste generation increased after the intensification of activities in the Boardwalk as the main problems in this environment. To this end, the need for environmental management measures, which includes the diagnosis, planning and managing activities that implement uses of this ecosystem.
Environmental management in leisure and tourism spaces in Lagoa do Apodi / RN
Monografia
Keywords: Usos dos recursos hídricos; espaços recreativos; Sustentabilidade; Uses of water resources; recreational spaces; sustainability; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA